Exploring the potential of a thermosensitive in situ gel with Periplaneta americana extracts for efficient wound healing - Liu, Shuai; Xu, Shuohan; Lu, Hang; Gong, Xueyu; Li, Huaipeng; Fan, Xinyu; Yang, Hongwei (Frontiers in Pharmacology, 2025)
The primary aim of this study was to fabricate a wound healing thermosensitive in situ gel containing Periplaneta americana extract (PAE), which is widely utilized clinically due to its anti-inflammatory and skin regeneration effects. The thermosensitive in situ gel was prepared using F127 and F68 at concentrations of 17.5% (w/v) and 3.75% (w/v) respectively. The physicochemical properties of the PAE-loaded gel was characterized by DSC, scanning electron microscopy, and FTIR. Additionally, the in vitro release behavior and the in vivo wound healing effects were also investigated. It was observed that the thermosensitive in situ gel exhibited a sol-gel transition temperature of approximately 32.5 °C ± 0.4 °C, and the PAE existed in an amorphous state within the lyophilized gel. FTIR spectra indicated the formation of hydrogel bonds between PAE and F127/F68, signifying a sustained release profile. Further in vivo wound healing and inflammatory cytokine experiments revealed that the drug-loaded hydrogel demonstrated superior wound healing activity compared to other counterparts, by accelerating the reduction of endogenous inflammatory mediators such as TNF-α, MMP9, and IL-6, and inhibiting the MAPK/NF-κB pathway. The PAE-loaded thermosensitive in situ gel represents a promising pharmaceutical candidate for local wound healing applications, owing to its prolonged retention time.